Pathogenic variability of Xanthomonas oryzae pv. oryzae - and N. LAKPALE, ARVIND KUMAR*, M.N. SRIVASTAVA (Indian Phytopathology, 2002)
Comparison of isolates of Xanthomonas oryzae pv. oryzae on a set of isogenic rice lines under greenhouse conditions revealed that the isolates prevalent in eastern Madhya Pradesh were more virulent than those prevalent in the Punjab, India. Comparison of eastern Madhya Pradesh isolates of X. oryzae pv. oryzae on a set of differentials with isolates prevalent in the Philippines and Japan revealed differences in the pathogenicity of these isolates.